Places and Spaces - UNICEF Innocenti Research Centre (United Nations, 2022)
Report Card 17 explores how 43 OECD/EU countries are faring in providing healthy environments for children. Do children have clean water to drink? Do they have good-quality air to breathe? Are their homes free of lead and mould? How many children live in overcrowded homes? How many have access to green play spaces, safe from road traffic? Data show that a nation’s wealth does not guarantee a healthy environment. Far too many children are deprived of a healthy home, irreversibly damaging their current and future well-being. Beyond children’s immediate environments, over-consumption in some of the world’s richest countries is destroying children’s environments globally. This threatens both children worldwide and future generations. To provide all children with safe and healthy environments, governments, policymakers, businesses and all stakeholders are called to act on a set of policy recommendations.